EFFECT OF CHICKPEA LEAVES (Vigna sinensis) FERMENTED IN FEED ON GROWTH OF GREEN CATFISH (Hemibagrus nemurus) FRY - Frenson Sarmento Sihombing; Adelina '; Nuraini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The aims of this research was to determine the response of green catfish (Hemibagrus nemurus) fry on the use of chickpea leaves (Vigna sinensis)  fermented in the feed to spurred growth and feed efficiency and to find out the best given percentage of chickpea leaves to the maximum growth of green catfish fry. This research used Completely Randomized Design (CRD) with one factor, five treatments and three replications. The substitution ratio of soybean flour with chickpea leaves flour were P1=100% : 0%; P2 = 95% : 5%; P3 = 90% : 10%; P4 = 85% : 14% and P5 = 80% : 20%. The parameters were observed  concsist of digestibility of feed, feed efficiency, protein retention and specific growth rate of green catfish fry. The  result showed that the chickpea leaves fermented in feed can replace soybean flour as a protein source in green catfish feed. The treatment in P4 (85% - 15%) were the best treatment with digestibility of feed 45,95%, feed efficiency 34,25%, protein retention 26,98% specific growth rate 4,18% and for feed cost analysis was Rp.7960   Keyword : Chickpea leaves, Feed, Hemibagrus nemurus.